Interior Design of Omah Blues in Surakarta - Raden Gasta Mulyandra Jayaatmaja; Ahmad Fajar Ariyanto (Pendhapa, 2022)
Surakarta is the heart of Javanese culture; hence the people of Surakarta are closely connected to artistic activities. There are various types of arts, one of which is performing arts. The many performances held in Surakarta are one of the city government's efforts to meet the needs of its people. One of the many performances is the Solo Blues Festival, which started in 2013, and every year the enthusiasm for the Solo Blues Festival increases. The event's success was also due to the role of the blues community in Surakarta. They are involved in the Solo Blues Festival and have a fixed agenda to perform and introduce blues music to the public. However, in Surakarta, there is not yet a specific place regarding blues music to serve as a place for activists and fans of blues music to get to know blues music more deeply. Community members are still constrained to introduce blues music to the public if they only rely on the concerts they organize. Based on the problems that occur, one solution to overcome them is to design a place specifically for blues music, namely Omah Blues. The interior design of Omah Blues in Surakarta will function as a place for blues music to continue to exist and develop in Surakarta. It is hoped that Omah Blues can also represent how blues music exists and develops in society, especially among the people of Surakarta City. The interior design of Omah Blues in Surakarta will apply an art deco style combined with the kawung batik motif as a design idea. The choice of art deco was due to the rapid development of blues music in harmony with the development of the art deco style. The choice of the kawung motif as the design idea is because the kawung motif is geometric, which is in line with art deco characteristics, as well as to bring out Javanese cultural identity.Kata Kunci : Interior, Blues, Art Deco, Kawung.